Pengaruh Harga, Kualitas Produk dan Kualitas Pelayanan Terhadap Loyalitas Konsumen dengan Kepuasan Konsumen Sebagai Variabel Intervening pada Resto Bebek Teman Ayam (BTA) Corner Tulungagung - Novinda Nurbiatul Elyana; Ali Mauludi AC (J-MAS (Jurnal Manajemen dan Sains), 2023)
The aims of this study are 1) to measure the direct and indirect effects of price, product quality and service quality on consumer loyalty with consumer satisfaction as the intervening variable. 2) To find out the total amount of each effect of the price variable, product quality and service quality for consumers of BTA Corner Tulungagung Resto. The approach of this research is a quantitative approach, this type of research is comparative causal. The data analysis technique of this study is multiple linear regression. Comparative causal research is research that is used to compare which effect is the strongest between the direct or indirect effect of each independent variable on the dependent variable and compares the total effect of each independent variable. The population of this study are consumers who have made purchases at BTA Corner Tulungagung Resto. The amount is not known with a sample of 100 respondents. The sampling method is by filling out questionnaires that are distributed online and offline with the target being consumers of Resto BTA Corner Tulungagung. The test results in this study indicate that price has a significant positive effect on customer satisfaction, price has a significant positive effect on customer loyalty, product quality has a significant positive effect on customer satisfaction, product quality has no effect on customer loyalty, service quality has no effect on customer satisfaction, service quality does not have an effect on customer loyalty, customer satisfaction has a significant positive effect on customer loyalty, customer satisfaction cannot have an effective effect in mediating price and service quality on customer loyalty, and customer satisfaction can have an effective influence in mediating product quality on consumer loyalty.